Genome-wide analysis of respiratory burst oxidase homolog (Rboh) genes in Aquilaria species and insight into ROS-mediated metabolites biosynthesis and resin deposition - Begum, Khaleda; Das, Ankur; Ahmed, Raja; Akhtar, Suraiya; Kulkarni, Ram; Banu, Sofia (Frontiers in Plant Science, 2024)
Respiratory burst oxidase homolog (Rboh) generates reactive oxygen species (ROS) as a defense response during biotic and abiotic stress. In Aquilaria plants, wounding and fungal infection result in biosynthesis and deposition of secondary metabolites as defense responses, which later forms constituents of fragrant resinous agarwood. During injury and fungal invasion, Aquilaria tree generates ROS species via the Rboh enzymes. Despite the implication of Rboh genes in agarwood formation, no comprehensive genomic-level study of the Rboh gene family in Aquilaria is present. A systematic illustration of their role during stress and involvement in initiating signal cascades for agarwood metabolite biosynthesis is missing. In this study, fourteen Rboh genes were retrieved from genomes of two Aquilaria species, A. agallocha, and A. sinensis, and were classified into five groups. The promoter regions of the genes had abundant of stress-responsive elements. Protein-protein network and in-silico expression analysis suggested their functional association with MAPK proteins and transcription factors such as WRKY and MYC2. The study further explored the expression profiles of Rboh genes and found them to be differentially regulated in stress induced callus and stem tissue, suggesting their involvement in ROS generation during stress in Aquilaria.Overall, the study provides in-depth insight into two Rboh genes, AaRbohC and AaRbohA, highlighting their role in defense against fungal and abiotic stress, and likely during initiation of agarwood formation through modulation of genes involved in secondary metabolites biosynthesis. The findings presented here offer valuable information about Rboh family members, which can be leveraged for further investigations into ROS-mediated regulation of agarwood formation in Aquilaria species.